Pengaruh Kompos Terhadap Pertumbuhan Dan Hasil Padi Varietas Ciherang Di Desa Mengkunyit - Eko Aprianto; Purwaningsih Purwaningsih; Kiswan Muhammad (Jurnal Sains Pertanian Equator, 2014)
It is well known that indonesion farmer always not putting organik watter in the soil. The aim of this research to determined of effect compost on grown and yield of paddy. The  experiment  use randomized block design, which  6 treatments and 4 replications with 5 plant sample. The treatments consisting  k0 = whithout compost; k1 = 8 kg compost / plot; k2 =10 kg compost / plot; k3 = 12 kg compost / plot;  k4 =14 kg compost / plot; and k5 :16 kg compost / plot. Height plant, maximum number of tillers, number of productif tiller, number of pannicle, pannicle density, procentation of filled grain and weight of grain was determined.The  results of this study showed no significant for all variable. Keywords : Compost, Growth, Yield, Variety Ciherang